Some Identities of the Twisted 𝑞-Genocchi Numbers and Polynomials with Weight 𝛼 and 𝑞-Bernstein Polynomials with Weight 𝛼 - H. Y. Lee; N. S. Jung; C. S. Ryoo (Abstract and Applied Analysis)
Recently mathematicians have studied some interesting relations between 𝑞-Genocchi numbers, 𝑞-Euler numbers, polynomials, Bernstein polynomials, and 𝑞-Bernstein polynomials. In this paper, we give some interesting identities of the twisted 𝑞-Genocchi numbers, polynomials, and 𝑞-Bernstein polynomials with weighted 𝛼.